The relationship between photometric and spectroscopic oscillation amplitudes from 3D stellar atmosphere simulations. Issue 1 (6th February 2021) - Zhou, Yixiao; Nordlander, Thomas; Casagrande, Luca; Joyce, Meridith; Li, Yaguang; Amarsi, Anish M; Reggiani, Henrique; Asplund, Martin
ABSTRACT: We establish a quantitative relationship between photometric and spectroscopic detections of solar-like oscillations using ab initio, 3D, hydrodynamical numerical simulations of stellar atmospheres. We present a theoretical derivation as a proof of concept for our method. We perform realistic spectral line formation calculations to quantify the ratio between luminosity and radial velocity amplitude for two case studies: the Sun and the red giant ϵ Tau. Luminosity amplitudes are computed based on the bolometric flux predicted by 3D simulations with granulation background modelled the same way as asteroseismic observations. Radial velocity amplitudes are determined from the wavelength shift of synthesized spectral lines with methods closely resembling those used in Birmingham Solar Oscillations Network (BiSON) and Stellar Oscillations Network Group (SONG) observations. Consequently, the theoretical luminosity to radial velocity amplitude ratios are directly comparable with corresponding observations. For the Sun, we predict theoretical ratios of 21.0 and 23.7 ppm [m s −1 ] −1 from BiSON and SONG, respectively, in good agreement with observations 19.1 and 21.6 ppm [m s −1 ] −1 . For ϵ Tau, we predict K2 and SONG ratios of 48.4 ppm [m s −1 ] −1, again in good agreement with observations 42.2 ppm [m s −1 ] −1, and much improved over the result from conventional empirical scaling relations that give 23.2 ppm [m s −1 ] −1 . This study thus opens the path towards a quantitative understanding of solar-like oscillations, via detailed modelling of 3D stellar atmospheres.